A three-dimensional coordination polymer with high proton conductivity and its preparation method and application

By designing a three-dimensional coordination polymer {[Cu3(OH)(btb)2(H2O)(HP2Mo5O23)]·6H2O}n and a composite membrane with Nafion, the problem of impaired proton conductivity of traditional proton exchange membrane fuel cells under high or low temperature conditions is solved, efficient proton conductivity is achieved, and the commercial application of fuel cells is promoted.

CN116239787BActive Publication Date: 2025-03-25HENAN UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310270861.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-03-25
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

In existing proton exchange membrane fuel cells, traditional perfluorosulfonated polymers such as Nafion are damaged in high or low temperature conditions, and are costly and complex in synthesis processes, making it difficult to explore their proton conduction behavior.

Method used

A three-dimensional coordination polymer {[Cu3(OH)(btb)2(H2O)(HP2Mo5O23)]·6H2O}n was developed to form an efficient proton conduction path through the coordination structure of CuII ions, btb ligands and [Mo5O15(PO4)(HPO4)]5-ion, and mixed with Nafion to prepare composite membranes to improve proton conductivity.

Benefits of technology

The three-dimensional coordination polymer and composite membrane exhibit significant proton conductivity under high temperature and high humidity conditions, close to the performance of commercial Nafion, which helps to achieve commercial application of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116239787B_ABST
    Figure CN116239787B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of coordination polymers, and specifically relates to a three-dimensional coordination polymer with high proton conductivity and a preparation method and application thereof. The chemical formula of the three-dimensional coordination polymer is: {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n , btb is 1,3-di(4-hydro-1,2,4-triazole-4-yl)benzene, and the three-dimensional coordination polymer belongs to the triclinic system, P ‒1 space group, unit cell parameters: a =12.354(5)Å, b =12.473(5)Å, c =16.411(6)Å, α =83.430(12)°, β =78.700(12)°, c =63.368(10)°. The three-dimensional coordination polymer of the present invention and the composite membrane prepared therefrom have high proton conductivity and are highly potential proton conducting materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coordination polymers, and in particular relates to a three-dimensional coordination polymer with high proton conductivity, a preparation method and an application thereof. Background Art

[0002] Fuel cells directly convert renewable chemical energy into electrical energy, have high theoretical efficiency and power density, and are a very promising environmentally friendly power generation device. The current fuel cells mainly include: proton exchange membrane fuel cells (PEMFCs); phosphoric acid fuel cells (PAFCs); solid oxide fuel cells (SOFCs) and alkaline fuel cells (AFC). Among them, proton exchange membrane fuel cells are considered to be the most promising candidate to replace traditional energy due to their outstanding advantages such as green and high efficiency, ultra-low emissions, high power density, and fast startup speed. In a typical H2 / O2 proton exchange membrane fuel cell device, H2 is oxidized at the anode to generate H + Protons are generated, and the generated electrons are transferred to the cathode through an external circuit, thereby generating current. At the same time, hydrogen protons pass through the proton exchange membrane (PEM) to the cathode, converting chemical energy into electrical energy. Since the only product is water, this conversion system is considered to be a clean and sustainable technology. In proton exchange membrane fuel cells, the proton exchange membrane, as the core component of the entire system, needs to meet several conditions: high proton conductivity (>10 -2 Scm -1 ); good chemical and thermal stability; excellent gas barrier performance; good membrane (film) mechanical properties and processing performance; good compatibility with other components such as bipolar plates and electrode materials; low cost; easy to mass produce. The first application in fuel cells was Nafion, a perfluorosulfonated polymer produced by DuPont in 1960. It has excellent proton conductivity (10 -1 -10 -2 S cm -1 ), however, its temperature range of use has certain limitations. When the temperature is greater than 80°C or lower than -5°C, the proton conductivity will be destroyed. In addition, its high cost and complex synthesis process further limit its application. On the other hand, as an amorphous material, it is difficult to explore its proton conduction behavior and proton transport path. Therefore, the development of new, low-cost and high-performance crystalline proton conductive materials has become a hot research topic in the field of chemistry.

[0003] In recent years, some crystalline materials have attracted wide attention due to their potential applications in proton exchange membrane fuel cells, such as metal organic frameworks, hydrogen bonded organic frameworks, etc. Among them, coordination polymers based on polyoxometalates have structural designability and adjustability, and can be used to design and synthesize crystalline materials with excellent proton conductivity through functionalized reactants; in addition, they can accurately perform structural analysis through X-ray single crystal technology and intuitively detect their proton transport paths, thereby further determining the relationship between structure-proton conduction function, revealing the mechanism of proton conduction, and providing a theoretical basis for further designing and synthesizing materials with high proton conductivity. At present, there are few reports on the modification of Nafion membranes with coordination polymer materials based on polyoxometalates to improve their proton conductivity. Summary of the invention

[0004] The present invention provides a three-dimensional coordination polymer with high proton conductivity and a preparation method and application thereof. The three-dimensional coordination polymer of the present invention and the composite membrane prepared therefrom have high proton conductivity and are highly potential proton conduction materials.

[0005] The present invention specifically adopts the following technical solutions:

[0006] The chemical formula of the three-dimensional coordination polymer is: {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n , where n represents an infinitely extended structure, btb is 1,3-di(4-hydro-1,2,4-triazole-4-yl)benzene, and the three-dimensional coordination polymer belongs to the triclinic system, P-1 space group, and the unit cell parameters are: α=83.430(12)°, β=78.700(12)°, γ=63.368(10)°.

[0007] The three-dimensional coordination polymer has an asymmetric unit, which contains three crystallographically independent Cu II ion, two btb ligands, one [Mo5O 15 (PO4)(HPO4)] 5– ion, one OH - , one coordinated water molecule and six free water molecules.

[0008] Three Cu II The ions show a tetrahedral configuration, with three Cu II The ions are Cu1, Cu2 and Cu3, Cu1 and two N atoms of two btb ligands, two [Mo5O 15 (PO4)(HPO4)] 5– The two O atoms and one OH -Coordinated, Cu2 and two N atoms of two btb ligands, one [Mo5O 15 (PO4)(HPO4)] 5– An O atom, an OH atom - Coordinate with one water molecule, Cu3 with three N atoms of three btb ligands, one OH - Coordinated with a water molecule, the bond lengths of Cu–O and Cu–N range from

[0009] Three Cu II Ions pass through a μ3-OH – The trinuclear Cu3(OH) units are connected, with Cu–O–Cu bond angles of 109.6°, 117.0°, and 118.0°, and Cu···Cu spacing of and The trinuclear Cu3(OH) units are linked by two tridentate and one tetradentate btb ligands to form a one-dimensional chain, which is further linked by [Mo5O 15 (PO4)(HPO4)] 5– The P–O and Mo–O in the ions are connected to form a two-dimensional layer structure, and the two-dimensional layer structure is connected by Mo–O–Cu to form a three-dimensional structure.

[0010] The preparation method of the above three-dimensional coordination polymer comprises:

[0011] Combine Cu(NO3)2·3H2O, H3PMo 12 O 40 A mixture of btb and distilled water is put into a reactor, the pH of the mixture is adjusted to 3.5-4.0, the temperature of the reactor is maintained at 160°C and heated for four days, cooled to room temperature, filtered and dried to obtain the product.

[0012] Wherein, the Cu(NO3)2·3H2O, H3PMo 12 O 40 The molar ratio of btb is 0.3:0.05:0.1, and each millimole of H3PMo 12 O 40 Add 120 mL of distilled water.

[0013] The present invention also provides a composite membrane, which is prepared from the three-dimensional coordination polymer.

[0014] The method for preparing the composite film comprises:

[0015] {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} nThe powder and the Nafion solution are uniformly mixed and stirred, and then the mixture is coated on a plate to form a film structure and dried at 60° C. to obtain a composite membrane.

[0016] The {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The mass ratio of the powder to the Nafion in the Nafion solution is 10:22.

[0017] The present invention is directed to the compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The powder was tested for proton conductivity and it was found that at 298K, as the relative humidity increased from 55% to 98%, the conductivity of the compound continued to increase, from 3.48×10 -11 S cm -1 to 3.05×10 -5 S cm -1 , increasing by six orders of magnitude. When the relative humidity is 98% and the temperature is continuously increased to 358K, the proton conductivity of the compound reaches 2.57×10 -4 S cm -1 .

[0018] The present invention converts the compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The powder was mixed with Nafion to prepare a sample-Nafion composite membrane, and the proton conductivity test was performed. The results showed that the proton conductivity of the composite membrane was 7.01×10 -6 S cm -1 As the relative humidity increases, the proton conductivity reaches 3.81×10 -3 S cm -1 , which increases by three orders of magnitude. When the temperature rises to 358K, the proton conductivity of the composite reaches 1.28×10 -2 S cm -1 .

[0019] Therefore, the three-dimensional coordination polymer and composite membrane of the present invention can be used to prepare proton conducting materials.

[0020] The beneficial effects of the present invention are:

[0021] The three-dimensional coordination polymer {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O}n With a new structure, the powder proton conductivity of the compound reached 2.57×10 at 358K and 98% RH. -4 S cm -1 The proton conductivity of the composite membrane reached 1.28×10 -2 S cm -1 , close to the proton conductivity of commercial Nafion, which will help realize the commercial application of proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 (a) Cu in compounds II (a) the coordination environment of the ion; (b) the two-dimensional layer structure of the compound; (c) the three-dimensional structure of the compound.

[0023] Figure 2 (a) Nyquist plot of the compound under 55%-98% RH and 298K; (b) Nyquist plot of the compound under 308-358K and 98% RH; (c) ln(σT) vs. 1000 / T curve; (d) PXRD pattern of the compound before and after proton conductivity test.

[0024] Figure 3 Infrared spectrum of the composite film.

[0025] Figure 4 (a) Nyquist plot of the composite film under 55%-98% RH and 298K; (b) Nyquist plot of the composite film under 308-358K and 98% RH; (c) ln(σT) vs.1000 / T curve. DETAILED DESCRIPTION

[0026] The present invention is described in more detail below through specific implementation modes to facilitate understanding of the technical solution of the present invention, but is not intended to limit the protection scope of the present invention.

[0027] 1.{[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n Synthesis of:

[0028] Combine Cu(NO3)2·3H2O (0.073g, 0.3mmol), H3PMo 12 O 40A mixture of (0.091 g, 0.05 mmol), btb (0.021 g, 0.1 mmol) and 6 mL of distilled water was placed in a 25 mL polytetrafluoroethylene stainless steel reactor. The pH of the mixture was adjusted to 3.5-4.0 with 2M HCl solution. The temperature of the reactor was maintained at 160°C for four days, cooled to room temperature, filtered and dried to obtain blue block crystals (yield: 27.8% based on btb). Elemental analysis (%): Theoretical value: C, 14.39; H, 1.93; N, 10.07. Expected value: C, 13.75; H, 1.64; N, 9.95. Infrared spectrum data (KBr, cm -1 ): 3395(s), 3060(s), 2929(s), 1616(m), 1549(s), 1250(m), 1106(s), 1070(s), 1019(s), 918(s), 873(s), 699(s), 671(s), 627(m). Among them: btb represents 1,3-di(4-hydro-1,2,4-triazol-4-yl)benzene.

[0029] 2.{[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n Determination of structure

[0030] Select the appropriate size of {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The single crystal was analyzed by X-ray diffraction on a Bruker Apex-II CCD diffractometer at a test temperature of 242(2)K. The crystal diffraction point data were collected using graphite-monochromatized MoKα rays (λ=0.071073nm), and the data were reduced and absorption corrected by the direct method. The structure was solved and refined using the SHELXS-2014 and SHELXL-2014 programs. The coordinates of non-hydrogen atoms in the structure were corrected for anisotropic temperature factors using the full matrix least squares method, and the coordinates of hydrogen atoms were obtained by theoretical hydrogenation. Compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The crystallographic data are shown in Table 1 below.

[0031] Table 1{[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n Crystallographic data

[0032]

[0033] 3.{[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n Structural analysis

[0034] X-ray single crystal diffraction analysis showed that the compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n It crystallizes in the triclinic system, P-1 space group. The asymmetric unit of this compound contains three crystallographically independent Cu II ion, two btb ligands, one [Mo5O 15 (PO4)(HPO4)] 5– ion, one OH - , one coordinated water molecule and six free water molecules. Figure 1 As shown in a, three Cu II The ion shows a tetrahedral configuration, with Cu1 and two N atoms of the two btb ligands, two [Mo5O 15 (PO4)(HPO4)] 5– The two O atoms and one OH - Coordinated, Cu2 and two N atoms of two btb ligands, one [Mo5O 15 (PO4)(HPO4)] 5– An O atom, an OH atom - Coordinate with one water molecule, Cu3 with three N atoms of three btb ligands, one OH - and one water molecule. The bond lengths of Cu–O and Cu–N range from and

[0035] Three Cu II Ions pass through a μ3-OH – The trinuclear Cu3(OH) units are connected, with Cu–O–Cu bond angles of 109.6°, 117.0°, and 118.0°, and Cu···Cu spacing of and The trinuclear Cu3(OH) unit is formed by two trinuclear

[0036] The tetradentate btb ligand is connected to form a one-dimensional chain, which is further connected by [Mo5O 15 (PO4)(HPO4)] 5– The P–O and Mo–O in the ions are connected to form a two-dimensional layer structure (such as Figure 1 b), the two-dimensional layer structure is connected by Mo–O–Cu to form a three-dimensional structure (as shown in Figure 1 c).

[0037] 4. Compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n Powder proton conductivity test

[0038] The compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The crystals were ground into powder, and the powder sample was placed on a tablet press mold with a diameter of 3 mm. It was pressed with a pressure of 0.5 MPa for about two minutes to obtain a disc with a thickness of 1.3 mm. Conductive silver glue was evenly applied on the upper and lower sections of the disc, and it was fixed on the sample stage with gold wire for testing. The instrument used for the alternating current impedance (AC) test of the compound was a high-precision impedance gain phase analyzer (Solartron 1260 / 1296). The measurement frequency range was 0.01 to 10 MHz, the input voltage was 100 mV, the measurement temperature range was from 298 K to 358 K, and the relative humidity (RH) range was from 55% to 98%. Conductivity σ (S cm -1 ) is calculated by the formula σ=L / (RA), where L (cm) and A (cm 2 ) represent the thickness and cross-sectional area of ​​the wafer, respectively, and R (Ω) is the resistance value of the sample, which is obtained by simulating the impedance data in the Nyquist diagram using the Zview equivalent circuit method. a ) Through the Arrhenius formula σT=σ o exp(-E a / kT), where k is the Boltzmann constant (eV / k) and T (K) is the temperature.

[0039] like Figure 2 As shown in a, at 298K, as the relative humidity increases from 55% to 98%, the conductivity of the compound increases continuously, from 3.48×10 -11 S cm -1 to 3.05×10 -5 S cm -1 , increased by six orders of magnitude, indicating that humidity has a great influence on the test of proton conductivity. When the relative humidity is 98% and the temperature is continuously increased to 358K, the proton conductivity of the compound reaches 2.57×10 -4 S cm -1 (like Figure 2 b). In order to further explore the proton transport mechanism, the Arrhenius equation was used to fit the temperature-dependent proton conductivity, and [ln(σT)vs 1000T -1 ]Drawing( Figure 2 c) Calculate the activation energy E of the compounda is 0.37eV, which follows the Grotthuss mechanism. In addition, the samples after the proton conductivity test were tested by X-ray powder diffraction (PXRD), such as Figure 2 As shown in Figure d, the position of the peak in the XRD spectrum is basically consistent with the theoretical peak of the XRD spectrum obtained by single crystal data simulation, indicating that the structure of the compound has not changed after the test.

[0040] 5. Preparation of Composite Membranes

[0041] 40 mg of compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The powder sample was uniformly mixed with 1.0 mL of 5 wt% Nafion solution and stirred for 3 hours. The mixture was then transferred to a glass plate and a rectangular film with a thickness of 9 μm was prepared using a scraping machine. The thickness was measured with a vernier caliper and then placed in a 60°C vacuum drying oven to obtain a composite membrane.

[0042] 6. Composite membrane proton conductivity test

[0043] In order to study the compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The composite membrane was tested for proton conductivity and the potassium bromide tableting method was used to test the application performance of the composite membrane at 400-4000 cm -1 The infrared spectra of the compounds and composite films were tested in the range of 1.17 W using a Bruker VERTEX-70 Fourier transform infrared spectrometer. Figure 3 As shown in the figure, the composite membrane shows infrared characteristic peaks of the compound and Nafion, indicating that the composite membrane was successfully prepared. We also conducted a proton conductivity test on the composite membrane. Figure 4 As shown in a, the proton conductivity of the composite at 298K and 55% RH is 7.01×10 - 6 S cm -1 As the relative humidity increases, the proton conductivity reaches 3.81×10 -3 Scm -1 , increased by three orders of magnitude. Figure 4 As shown in b, when the temperature rises to 358K, the proton conductivity of the composite reaches 1.28×10 -2 S cm -1 The activation energy E of the composite film was obtained by fitting the Arrhenius formula. a is 0.24eV (such as Figure 4c), which follows the Grotthuss mechanism.

[0044] As energy and environmental issues become increasingly serious, it is very important to develop green, environmentally friendly and efficient fuel cell technology. Proton exchange membrane fuel cells have attracted widespread attention due to their ultra-low emissions, high power density and fast startup speed. As the core component of proton exchange membrane fuel cells, one of the primary characteristics of proton exchange membrane is its high proton conductivity. Compound {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The proton conductivity of the powder reached 2.57×10 at 358K and 98% RH. -4 S cm -1 The proton conductivity of the composite membrane reached 1.28×10 -2 S cm -1 Therefore, this compound is a highly potential proton conducting material.

[0045] The embodiments described above are only preferred embodiments of the present invention and are not intended to limit the scope of implementation of the present invention. Therefore, any equivalent changes or modifications made according to the structures, features and principles described in the patent scope of the present invention should be included in the scope of the patent application of the present invention.

Claims

1. A three-dimensional coordination polymer with high proton conductivity, characterized in that: The chemical formula of the three-dimensional coordination polymer is: {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n , btb is 1,3-di(4-hydro-1,2,4-triazol-4-yl)benzene, and the three-dimensional coordination polymer belongs to the triclinic system, P ‒1 space group, unit cell parameters: a =12.354(5)Å, b =12.473(5)Å, c =16.411(6)Å, α =83.430(12)°, β =78.700(12)°, γ =63.368(10)°; the three-dimensional coordination polymer has an asymmetric unit, which contains three crystallographically independent Cu II ion, two btb ligands, one [Mo5O 15 (PO4)(HPO4)] 5‒ ion, one OH ‒ , one coordinated water molecule and six free water molecules.

2. A three-dimensional coordination polymer with high proton conductivity according to claim 1, characterized in that: Three Cu II The ions show a tetrahedral configuration, with three Cu II The ions are Cu1, Cu2 and Cu3, Cu1 and two N atoms of two btb ligands, two [Mo5O 15 (PO4)(HPO4)] 5– The two O atoms and one OH ‒ Coordinated, Cu2 and two N atoms of two btb ligands, one [Mo5O 15 (PO4)(HPO4)] 5– An O atom, an OH atom ‒ Coordinate with one water molecule, Cu3 with three N atoms of three btb ligands, one OH ‒ Coordinated with a water molecule, the bond lengths of Cu–O and Cu–N range from 1.919(8) Å to 2.397(14) Å and 1.972(11) Å to 2.010(11) Å.

3. The method for preparing the three-dimensional coordination polymer according to claim 1, characterized in that: include: Combine Cu(NO3)2·3H2O, H3PMo 12 O 40 A mixture of btb and distilled water is put into a reactor, the pH of the mixture is adjusted to 3.5-4.0, the temperature of the reactor is maintained at 160°C and heated for four days, cooled to room temperature, filtered and dried to obtain the product.

4. The preparation method according to claim 3, characterized in that: The Cu(NO3)2·3H2O, H3PMo 12 O 40 The molar ratio of btb is 0.3:0.05:0.1, and each millimole of H3PMo 12 O 40 Add 120 mL of distilled water.

5. A composite film, characterized in that The composite membrane is prepared from the three-dimensional coordination polymer described in any one of claims 1 to 3.

6. The method for preparing the composite film according to claim 5, characterized in that: {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The powder and the Nafion solution are uniformly mixed and stirred, and then the mixture is coated on a plate to form a film structure and dried at 60° C. to obtain a composite membrane.

7. The preparation method according to claim 6, characterized in that: The {[Cu3(OH)(btb)2(H2O)(HP2Mo5O 23 )]·6H2O} n The mass ratio of the powder to the Nafion in the Nafion solution is 10:

22.

8. Use of the three-dimensional coordination polymer according to any one of claims 1 to 2 in the preparation of proton conducting materials.

9. Use of the composite membrane according to claim 5 in preparing proton conducting materials.

Citation Information

Patent Citations

  • Phosphomolybdic acid supramolecular polymer with water-assisted hydrogen bond conductive network structure

    CN114823156A